FIRM VALUE OF ISLAMIC BANKING IN INDONESIA: THE EFFECT OF RISK PROFILE AND INVESTMENT RISK WITH EFFICIENCY AS A MODERATING VARIABLE - Ahmad Zubair; Husaini; Jummaini; Hijri Juliansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Firm value is a fundamental aspect considered by investors when selecting investment targets. During 2024–2025, the firm value of Islamic banks in Indonesia experienced a decline, thereby motivating this study to examine the determinants of firm value in this sector. Specifically, the research investigates the influence of risk profile and investment risk on firm value, with efficiency serving as a moderating variable. This is a quantitative study based on secondary data obtained from the Indonesia Stock Exchange (IDX) and the Financial Services Authority (OJK). The sample consists of 204 observations covering the period 2021–2025. The findings reveal that the risk profile has no significant effect on firm value, while investment risk has a significant positive effect on the firm value of Islamic banks in Indonesia. Furthermore, efficiency functions as a moderating variable, categorized as a pure moderator, in the relationship between risk profile, investment risk, and firm value.